IMPLEMENTASI E-GOVERNMENT MELALUI APLIKASI SISTEM PENGELOLAAN ASET DESA (SIPADES) DI DESA DUKUHSARI KECAMATAN JABON KABUPATEN SIDOARJO - Aprillia Hartiningtyas; Ilmi Usrotin Choiriyah (Journal Publicuho, 2024)
The study aims to describe and analyze how implementation of e-government through the village asset management system application in the Dukuhsari Village Jabon District Sidoarjo Regency. The study uses qualitative descriptive data collection techniques through interviews, observation, and documentation. The data analysis model in this study is data collection, data reduction, data presentation, and drawing conclusions. Results from the study indicate that an organizational indicator, there is an organizational structure in the Dukuhsari Village government and the government has provided a facility for implementing the asset management system application, but there is still a lack of human resource capabilities. From the interpretation indicator in the socialization dimension, the policy has not been optimal because of the lack of suitable socialisation to so the operator does not understand the procedures for using the asset management system application. In the application dimension, it shows that the technical conditions experienced obstacles in the form of frequent application often errors during working hours thus disrupting the operator from inputting village assets into the asset management system application.